Atifa Towage & Transport Sdn Bhd / Anis Arlisha Mohamad Faisal - Mohamad Faisal, Anis Arlisha (Faculty of Business and Management, 2023)
An internship is the final course for all undergraduate programs in the faculty of Business and Management, according to the study plan. This internship course functions as a training ground for students to gain practical knowledge and workplace skills that provide experience with work and responsibility in completing company-assigned tasks. It would improve the practical skills, knowledge, and attitude required for completing the assignment. Therefore, I have successfully completed this Industrial Training Report for the company where I've been employed, Atifa Towage & Transport Sdn Bhd (ATTSB) Business Development Department. I began working for this company in 22th February 2023, and based on my observations, this is the best place to develop your career and skills. ATTSB focuses not only on constructing high-quality goods but also on its culture and environment. The departments are well-coordinated and have a patient culture, with management willing to provide opportunities and share information, allowing me to perform well. In conclusion, the company's business development department gave me the opportunity to gain practical experience. It is where I've been employed to in charge of generating corporate revenue through sales. This report has been divided into sections. The first part is about my profile, followed by the company's profile and its nature of organization. The next part is about my training reflection, where I will give further explanation regarding my working duration, details, and gains. Then is the SWOT analysis, where I will summarize the strengths, weaknesses, opportunities, and threats based on my experience and observations working there. Right after that, I will give my own recommendation on how to overcome the problems that arise in the organization and conclude the overall report.